Validation of the psychometric properties of the scale of resilience to suicide attempts among adolescents in Mainland China - Zhu, Li; Cheng, Wenqian; Huang, Yaoyao; Xin, Siying; Shu, Wan; Wang, Xiaoning; Zhang, Jinsheng; Li, Mei; Miao, QunFang (Frontiers in Psychiatry, 2025)
BackgroundSuicide resilience has garnered increasing attention from researchers due to its potential role in suicide prevention. In 2021, Sánchez-Teruel et al. developed a tool to assess the resilience levels of individuals with a history of suicide attempts. The Scale of Resilience to Suicide Attempts (SRSA) is composed of 18 items across three dimensions: internal protection, emotional stability, and external protection. While the scale has shown robust psychometric properties in Spanish-speaking populations, cultural differences call for a revalidation of its psychometric characteristics among suicide attempters in Mainland China.ObjectiveThis study aims to translate and adapt the SRSA into Chinese, and to evaluate its psychometric properties in adolescents who have attempted suicide in Mainland China.MethodsFollowing Brislin’s translation model, a survey was conducted using purposive sampling on 393 adolescents who had attempted suicide at the Hangzhou Normal University Affiliated Hospital and the Affiliated Mental Health Center of Zhejiang University School of Medicine. An expert panel evaluated the content validity. The scale’s structural validity was assessed through exploratory factor analysis and confirmatory factor analysis, along with measurement invariance. Additionally, tests for convergent validity, discriminant validity, and criterion-related validity were conducted. Reliability was evaluated using Cronbach’s alpha coefficient, McDonald’s omega, test-retest reliability, and split-half reliability.ResultsThe Chinese version of the SRSA comprises three dimensions and 16 items. The item-level content validity index for all items ranged from 0.88 to 1.00, while the Scale-Level Content Validity Index was 0.97. The three common factors explained a cumulative variance of 59.339%. Confirmatory factor analysis demonstrated a good model fit. The Cronbach’s alpha coefficient for the entire scale was 0.908, and McDonald’s omega was 0.910, with individual dimension Cronbach’s alpha values ranging from 0.780 to 0.869 and McDonald’s omega ranging from 0.859 to 0.910.ConclusionThe Chinese version of the SRSA is a valid and reliable tool for assessing the resilience levels of adolescents who have attempted suicide in Mainland China.